2013
DOI: 10.1248/bpb.b12-00859
|View full text |Cite
|
Sign up to set email alerts
|

Fimasartan, Anti-hypertension Drug, Suppressed Inducible Nitric Oxide Synthase Expressions <i>via</i> Nuclear Factor-Kappa B and Activator Protein-1 Inactivation

Abstract: Since inhibition of angiotensin II type 1 (AT1) receptor reduces chronic inflammation associated with hypertension, we evaluated the anti-inflammatory potential and the underlying mechanism of fimasartan, a Korean Food and Drug Administration approved anti-hypertension drug, in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Fimasartan suppressed the expressions of inducible nitric oxide synthase (iNOS) by down-regulating its transcription, and subsequently inhibited the productions of nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(38 reference statements)
0
14
0
1
Order By: Relevance
“…AT1 antagonists have been shown to attenuate inflammation and oxidative stress (Sharma and Singh, 2012;Bild et al, 2013), prevent the activation of nuclear factor-kappa B, and inhibit mRNA expression of interleukin (IL)-1β, IL-6, and TNF-α in microglia (Sharma and Singh, 2012;Ryu et al, 2013). Previous study had showed that angiotensin-converting enzyme type 2 (ACE2) decreased Ang II overproduction with ischemic injury in the model of ischemic, suggesting that ACE2 can protect against the effects of Ang II, and AII is in part a pharmacological consequence of brain injury (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…AT1 antagonists have been shown to attenuate inflammation and oxidative stress (Sharma and Singh, 2012;Bild et al, 2013), prevent the activation of nuclear factor-kappa B, and inhibit mRNA expression of interleukin (IL)-1β, IL-6, and TNF-α in microglia (Sharma and Singh, 2012;Ryu et al, 2013). Previous study had showed that angiotensin-converting enzyme type 2 (ACE2) decreased Ang II overproduction with ischemic injury in the model of ischemic, suggesting that ACE2 can protect against the effects of Ang II, and AII is in part a pharmacological consequence of brain injury (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To further study the mechanism by which activating or deactivating AT receptors results in a high bone-turnover state with osteoblastic and osteoclastic activity, osteoblasts and osteoclast precursors expressing AT receptors were used for in vitro cell viability and the osteogenic and osteoclastogenic assay [Nishiya and Sugimoto, 2001;Ryu et al, 2013]. As shown in Fig.…”
Section: Angii Affects Osteoblast and Osteoclast Precursor Viability mentioning
confidence: 99%
“…When the blood pressure and heart rate were stabilized, Ang II (0.1 µg/kg) was intravenously administered to the left femoral vein of rats three times with an interval of 20 min prior to treatment of test compounds to obtain the reference. Fimasartan (0.3, 1, or 3 mg/kg), losartan (1, 3, or 10 mg/kg) or vehicle distilled water (D.W.) were administered orally and then Ang II were intravenously treated as a bolus at various time points (20,40, 60 min, 1.5, 2, 3, 4, 5,6,8,10,12,16,20, and 24 h) to determine the Ang II-induced blood pressure response.…”
Section: Methodsmentioning
confidence: 99%